Physical activity participation by adults with cystic fibrosis: An observational study. Issue 3 (30th December 2015) - Cox, Narelle S.; Alison, Jennifer A.; Button, Brenda M.; Wilson, John W.; Morton, Judith M.; Holland, Anne E.
Abstract: Background and objective: Studies in children with cystic fibrosis (CF) suggest greater physical activity (PA) is associated with a slower rate of decline in respiratory function. In adults with CF, objectively measured PA time and its relationship to long‐term clinical outcomes of respiratory function and need for hospitalization are unknown. Methods: PA measured objectively (SenseWear armband), pulmonary function, exercise capacity (Modified Shuttle Test‐25) and CF‐related quality of life (CFQ‐R) were assessed in 65 adults (34 male; mean age 28 years) with CF during a stable phase. A sub‐group of these participants undertook additional measurement of PA at hospital discharge for a respiratory exacerbation. Results: Median daily habitual moderate‐vigorous PA (MVPA) time was 31‐min (IQR:15–53). Participants who accumulated ≥30‐min MPVA daily experienced fewer hospital days ( P = 0.04), better exercise capacity and higher FEV1 at 12 months ( P ≤ 0.001). Daily, fewer females than males accrued ≥30‐min MVPA ( P = 0.02). Compared with those who did not, participants who accumulated 30‐min MVPA in bouts ≥10‐min ( n = 21) recorded better FEV1 ( P = 0.02) and exercise capacity ( P = 0.006), and reduced hospital admissions ( P = 0.04) and hospital days ( P = 0.04) at 12 months. MVPA participation declined significantly 1 month post‐hospital discharge (median 12 min (4–34); P = 0.04). Conclusion: Adults with CF are able to achieve recommended MVPA targets of 30mins/day; however, a significant gender difference in activity time is apparent. Greater time in MVPA is related to more positive clinical outcomes over 12 months. Whether increasing PA levels can improve clinical outcomes in adults with CF warrants further investigation. See Editorial, page 404 Abstract : This observational study investigates patterns of physical activity in adults with cystic fibrosis (CF). Participants with higher levels of physical activity needed less hospital admission over 1 year. Adult females with CF had low levels of physical activity. See Editorial, page 404